Oil field chemicals - Fink, Johannes Karl (Gulf Professional Pub., 2003)
This book reviews the progress in the area of oil field chemicals and additives of the last decade from a rather chemical view. Provides the petroleum engineer involved with research and development with a quick reference tool.